Occupational Health in Mountainous Kyrgyzstan - Kenesh O. Dzhusupov (Ubiquity Press, 2015)
Background: In the period of transition from a centralized economy to the market economy, occupational health services in Kyrgyzstan have survived through dramatic, detrimental changes. It is common for occupational health regulations to be ignored and for basic occupational health services across many industrial enterprises and farms to be neglected. Objective: The aim of this study was to demonstrate the present situation and challenges facing occupational health services in Kyrgyzstan. Findings: The transition from centralized to the market economy in Kyrgyzstan has led to increased layoffs of workers and unemployment. These threats are followed by increased workload, and the health and safety of workers becomes of little concern. Private employers ignore occupational health and safety; consequently, there is under-reporting of occupational diseases and accidents. The majority of enterprises, especially those of small or medium size, are unsanitary, and the health status of workers remains largely unknown. The low official rates of occupational diseases are the result of data being deliberately hidden; lack of coverage of working personnel by medical checkups; incompetent management; and the poor quality of staff, facilities, and equipment. Because Kyrgyzstan is a mountainous country, the main environmental and occupational factor of enterprises is hypoxia. Occupational health specialists have greatly contributed to the development of occupational medicine in the mountains through science and practice. Conclusions: The enforcement of existing strong occupational health legislation and increased financing of occupational health services are needed. The maintenance of credible health monitoring and effective health services for workers, re-establishment of medical services and sanitary-hygienic laboratories in industrial enterprises, and support for scientific investigations on occupational risk assessment will increase the role of occupational health services in improving the health of the working population.